Pengembangan Media ReChap (Recount Chapter) Berbasis PowerPoint Hyperlink pada Mata Pelajaran Bahasa Inggris Kelas X di MA Al-Azhar Peterongan Jombang - Rohmawati, Harisma Dewi; Rohmah, Hidayatur (YASIN, 2025)
This study focuses on the development of RECHAP (Recount Chapter) learning media based on PowerPoint Hyperlink to enhance the effectiveness of English language learning for tenth-grade students at MA Al-Azhar Peterongan Jombang. The media was designed to help students understand Recount Text, particularly in mastering the use of Past Tense, through an interactive and engaging approach. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Validation results from content and media experts indicate that RECHAP achieved a high feasibility level, categorized as “highly feasible” for use. Student trials also generated positive responses, with a feasibility score of 88%, demonstrating that this media effectively enhances students’ motivation and comprehension of Recount Text materials. The study concludes that RECHAP, as a PowerPoint Hyperlink-based learning medium, is both feasible and effective for use in English instruction and offers an innovative alternative to support Recount Text comprehension at the madrasah aliyah level. The implications suggest that this medium can serve as a practical reference for teachers in presenting more interactive and contextual learning materials.